Adaptive fixed-time fault-tolerant trajectory tracking control for disturbed robotic manipulator. - Zeeshan Anjum; Zhe Sun; Saim Ahmed; Ahmad Taher Azar (PLoS ONE, 2025)
This article introduces a fixed-time trajectory control method for robotic manipulators, aimed at improving trajectory precision despite external disturbances, actuator faults, and uncertainties. Initially, a fast fixed-time nonsingular terminal sliding surface (FFNTSS) is utilized, featuring a bounded convergence time that remains unaffected by the initial conditions. This sliding surface not only prevents the occurrence of singularity but also guarantees fast convergence. Subsequently, building upon the FFNTSS and adaptive methodology, a novel approach termed continuous adaptive fixed-time nonsingular terminal sliding mode fault-tolerant control (CAFNTSMFTC) is introduced. According to the Lyapunov theorem, rigorous analysis demonstrates that the sliding mode variables and tracking errors of the closed-loop system converge to a small neighborhood of the origin within a fixed-time frame. Moreover, by approximating the square of the uncertainty's upper bound, the devised CAFNTSMFTC approach eliminates the need for the boundary layer commonly imposed in existing adaptive fixed-time control approaches. Lastly, comprehensive comparative simulations are conducted employing the PUMA560 robot. These simulations validate the proposed control strategy, underscoring its ability to achieve precise trajectory tracking and fast convergence, even when facing uncertainties, disturbances, and actuator faults. Moreover, the proposed control strategy for the robot manipulator is distinguished by its continuity and demonstrates dynamics in which chattering is mitigated.